2014
DOI: 10.1097/aln.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial Septum Motion but Not Doppler Assessment Predicts Elevated Pulmonary Capillary Wedge Pressure in Patients Undergoing Cardiac Surgery

Abstract: Doppler assessment of PCWP was neither sensitive nor specific enough to be clinically useful in anesthetized patients with mechanical ventilation. The fixed curve pattern of the interatrial septum was the best predictor of raised PCWP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Left ventricular systolic dysfunction was defined as systolic fractional reduction in LV internal dimension less than 24% or a reduction in LV end diastolic area less than 50%. Left ventricular diastolic dysfunction was defined as normal LV systolic function with raised left atrial pressure determined by the presence of a fixed curvature of the interatrial septum towards the right atrium, as demonstrated by Haji et al [22]. Right ventricular dysfunction was defined using ultrasound as dilation of the RV end-diastolic area to greater than two-thirds of the LV end-diastolic area and reduced RV free wall motion with or without flattening of the interventricular septum.…”
Section: Methodsmentioning
confidence: 99%
“…Left ventricular systolic dysfunction was defined as systolic fractional reduction in LV internal dimension less than 24% or a reduction in LV end diastolic area less than 50%. Left ventricular diastolic dysfunction was defined as normal LV systolic function with raised left atrial pressure determined by the presence of a fixed curvature of the interatrial septum towards the right atrium, as demonstrated by Haji et al [22]. Right ventricular dysfunction was defined using ultrasound as dilation of the RV end-diastolic area to greater than two-thirds of the LV end-diastolic area and reduced RV free wall motion with or without flattening of the interventricular septum.…”
Section: Methodsmentioning
confidence: 99%
“…In extreme conditions, severely impaired ventricular filling can be visualized as 'kissing walls' when the papillary muscles touch each other at end-systole corresponding to full emptying of the ventricle (parasternal short-axis view). Conversely, a high left ventricular filling pressure will facilitate a fixed bulging of the interatrial septum into the right atrium [33].…”
Section: Preloadmentioning
confidence: 99%
“…The interatrial septum should be examined as its motion correlates with filling pressure. 22,23 This is also an excellent view to assess the permeability of a patent foramen ovale by performing a bubble contrast study. Moving the ultrasound beam upward, a view of the RVOT can be obtained with the origin of the pulmonary valve.…”
Section: The Parasternal Viewsmentioning
confidence: 99%